تفاعل الثقافي والسياسي بالجزائر خلال الفترة العثمانية - خيواني فاتح; بن قويدر نورالدين (University of Eloued جامعة الوادي, 2024)
لم تكن الثقافة الجزائرية وليدة الصدفة في انبثاقها وبزوغ فجرها للعلن إنما كانت وليدة التجارب والتراكمات المحلية منها والمكتسبة طيلة قرون من التفاعل مع الحواضر الأخرى خلال فترات السلم والاستقرار التي فرضها الواقع السياسي؛ الذي مهد لهذا التفاعل أخذا وعطاء؛ على الوجه الذي يلبي الحاجة المادية والمعنوية للإنسان في المغرب الأوسط بشكل خاص في خضم تلك التقلبات. تفضي لنا هذه الدراسة عن حجم من البراعة والموهبة التي يتصف بها الفرد الجزائري من خلاله رصده واستيعابه لثقافات الأمم الاخرى في مختلف الظروف السياسية؛ بل تجاوز هذه الثقافات وبلور ثقافة جزائرية أصيلة كان للعثمانيين دور في تشكلها. Algerian culture was not the result of chance in its emergence and its dawning into the open, but it was the result of local experiences and accumulations from it and acquired over centuries of interaction with other cities during periods of peace and stability imposed by the political reality. who paved the way for this interaction, give and take; In a way that meets the material and moral needs of people in the Middle Maghreb, in particular, in the midst of these fluctuations. This study leads us to the extent of the ingenuity and talent that characterizes the Algerian individual through his monitoring and assimilation of the cultures of other nations in various political circumstances; Rather, it transcends these cultures and crystallizes an authentic Algerian culture, in which the Ottomans had a role to play..
المؤسسات الدينية والثقافية والسلطة الحاكمة
Keywords: العثمانيون; الجزائر; الثقافة; السياسة; المدارس